IL1R2, CCR2, and CXCR4 May Form Heteroreceptor Complexes with NMDAR and D2R: Relevance for Schizophrenia - Borroto-Escuela, Dasiel O.; Tarakanov, Alexander O.; Bechter, Karl; Fuxe, Kjell (Frontiers in Psychiatry, 2017)
The mild neuroinflammation hypothesis of schizophrenia was introduced by Bechter in 2001.It has been hypothesized that a hypofunction of glutamatergic signaling via N-methyl-n-aspartate receptors (NMDARs) and hyperactivation of dopamine D2 receptors play a role in schizophrenia. The triplet puzzle theory states that sets of triplet amino acid homologies guide two different receptors towards each other and contributes to the formation of a receptor heteromer. It is therefore proposed that putative NMDAR- C-C chemokine receptor type 2 (CCR2), NMDAR- C-X-C chemokine receptor type 4 (CXCR4) and NMDAR- Interleukin 1 receptor type II (IL1R2) heteromers can be formed in the neuronal networks in mild neuroinflammation due to demonstration of Gly-Leu-Leu (GLL), Val-Ser-Thr (VST) and/or Ser-Val-Ser (SVS) amino acid homologies between these receptor protomers. This molecular process may underlie the ability to produce symptoms of schizophrenia in mild neuroinflammation. In this state volume transmission is increased involving increased extracellular vesicle mediated volume transmission from microglia and astroglia. These vesicles may contain CCR2, CXCR4 and/or IL1R2 as well as their ligands and upon internalization by endocytic pathways into neurons can form heteroreceptor complexes with NMDAR in the plasma membrane with pathological allosteric receptor-receptor interactions involving increased internalization and reduced NMDAR signaling. The triplet puzzle theory also suggests the formation of putative D2R-CCR2, D2R-CXCR4 and D2R-IL1R2 heteromers in mild neuroinflammation in view of their demonstrated sets of Leu-Tyr-Ser (LYS), Leu-Pro-Phe (LPF) and/or Ser-Leu-Ala (SLA) triplet homologies. These D2R heteroreceptor complexes may also contribute to schizophrenia-like symptoms in mild neuroinflammation by enhancing D2R protomer function.